Entheseal involvement in systemic disorders. Issue 12 (December 2015) - Slobodin, Gleb; Rimar, Doron; Boulman, Nina; Kaly, Lisa; Rozenbaum, Michael; Rosner, Itzhak; Odeh, Majed
Abstract The objective of this study is to review the data on entheseal involvement in systemic disorders. A Pubmed search utilizing the indexing terms "enthesis" and "enthesitis" was conducted and the data pertinent to the aim of the review was extracted and organized in accordance with the preplanned structure of the manuscript. A number of cadaver-based studies, as well as studies using ultrasonography and magnetic resonance imaging, have detailed new distinct aspects of enthesis physiology and pathology in a variety of rheumatic and non-rheumatic systemic disorders. Major progress has been done in characterization of separate components of the enthesis organ, imaging of entheses, elaboration of the role and features of entheseal disease in spondyloarthropathies, juvenile idiopathic arthritis, osteoarthritis, familial Mediterranean fever, hyperuricemia, and other systemic conditions. The knowledge acquired and summarized herein shows that entheses can be affected in various ways in variety of medical disorders with different pathogenesis. Better understanding of the risk factors, mechanisms and natural history of enthesopathies is warranted. The current progress in the understanding of entheseal involvement in systemic disorders represents just the first step in resolving the entheses-related enigmas.